BOTOH DAN PRAKTIK VOTE BUYING PADA PILKADA KUDUS TAHUN 2024 - Salmadina Mutiara Latifa; Kushandajani Kushandajani (Journal of Politic and Government Studies, 2026)
Vote buying remains one of the most persistent forms of money politics in Indonesia’s local electoral democracy. This phenomenon does not only involve candidates and voters but also intermediaries who play a strategic role in connecting both actors. This study aims to analyze the working patterns and roles of Botoh in vote buying practices during the 2024 Kudus Regional Head Election. This research employs a qualitative descriptive approach. Data were collected through in-depth interviews with eight informants consisting of Botoh, village heads, political party elites, and field campaign teams. The data were complemented by relevant document analysis. The findings reveal that Botoh act as political brokers who connect candidates and voters through informal social networks. Botoh function not only as distributors of material incentives but also as managers of political information, voter mapping strategists, and controllers of field level electoral strategies. The working patterns of Botoh are characterized by opportunistic involvement based on electoral calculations, the use of layered survey mechanisms to identify voter preferences, selective and contextual distribution of incentives, and tacit coordination through the separation of operational channels between Botoh networks and formal campaign teams. The relationship between Botoh and candidates is informal and contractual, involving agreements regarding rewards after electoral victory. This study concludes that vote buying practices in the 2024 Kudus Regional Election operate through a structured brokerage mechanism in which Botoh play a central role in managing social networks, political information, and the distribution of electoral resources.